"We restrict certain things": a cross-sectional study of health provider adherence to WHO's recommendation for intrapartum oral intake of fluid and food in Greater Accra, Ghana - Benjamin Stephens; Pearl Nanka-Bruce; Habtamu Fekadu Lashtew (BMC, 2024)
Abstract Background Since 2018, WHO recommends oral fluid and food intake for low-risk women during labor to enhance positive childbirth experience and respect for women's preferences. This study investigated the current practices related to intrapartum oral intake among maternity care providers and women in public health facilities in Greater Accra, Ghana, and explored barriers and opportunities for adherence to the WHO guidance. Methods We used a mixed-method design at five public health facilities in Greater Accra, Ghana, which included structured interviews with 11 facility-level quality improvement staff and 12 maternity care providers; a knowledge, attitudes, and practices survey with the same providers; and a client survey with 56 inpatient postpartum women. We conducted descriptive and inferential statistics, including z-tests to assess independent and dependent variables, and inductive thematic analyses. Results Provider adherence to the WHO recommendation varied, with many imposing restrictions on oral intake during labor. Concerns included potential complications like Mendelson's syndrome, consequently framing oral intake decisions as clinical and leading providers to limit women's involvement in their care decisions. Within our sample, 54% and 43% women reported their provider counseled them on oral fluid and food intake respectively, while 41% and 34% reported their provider asked them their preference for drinking and eating respectively. Ultimately, 73% drank fluids and 19% ate food during their labor. Counseling significantly correlated with women's intake practices (p < 0.01) and providers' inquiry to women's preferences for drinking and eating (p < 0.001) during labor. Conclusion Adherence to evidence-based practices for intrapartum oral intake among low-risk women was inconsistence. Maternity care providers play a vital role in involving women in their care decisions and respecting women's preferences. Strengthening national-level labor care guidelines and provider quality improvement approaches like in-service training, supportive supervision, and job aides to include the WHO recommendation will help providers adhere to the guidance and contribute to promoting a positive childbirth experience for women.